1998
DOI: 10.1515/tjj.1998.15.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Physics Of Airfoil Clocking In A High-Speed Axial Compressor

Abstract: Axial compressors have inherently unsteady flow fields because of relative motion between rotor and stator airfoils. This relative motion leads to viscous and in viscid (potential) interactions between blade rows. As the number of stages increases in a turbomachine, the buildup of converted wakes can lead to progressively more complex wake/wake and wake/airfoil interactions. Variations in the relative circumferential positions of stators or rotors can change these interactions, leading to different unsteady fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The numerical results in a three-stage low-pressure turbine of Arnone et al [2] show similar trends as reported by Dorney et al [1]. The effect of full-clocking (clocking of both the rotor and stator blade rows) on the maximal efficiency variation was estimated to be 0.7 per cent.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The numerical results in a three-stage low-pressure turbine of Arnone et al [2] show similar trends as reported by Dorney et al [1]. The effect of full-clocking (clocking of both the rotor and stator blade rows) on the maximal efficiency variation was estimated to be 0.7 per cent.…”
Section: Introductionsupporting
confidence: 79%
“…In the past several decades, many researchers experimentally and numerically investigated the effect of clocking on the efficiency. Dorney et al [1] carried out the investigation of clocking on performance in a 1.5-stage compressor. The numerical results show that the improvement in efficiency with stator clocking is 0.6-0.7 per cent.…”
Section: Introductionmentioning
confidence: 99%
“…That the relation of clocking position and efficiency has a sinusoidal shape with typical variations within the range of 0.2 up to 2.7%, [13][14][15] is nowadays commonly accepted. [16][17][18] However, controversial findings have been reported regarding the optimal impingement location of the upstream stator wake on the downstream stator vane to maximise efficiency. For example, Gundy-Burlet et al 19 and Dorney et al 17 concluded that the optimal combination of high efficiency occurred when the upstream stator wake was convected along the pressure surface of the downstream stator.…”
Section: Guide Vane Rotormentioning
confidence: 99%
“…[16][17][18] However, controversial findings have been reported regarding the optimal impingement location of the upstream stator wake on the downstream stator vane to maximise efficiency. For example, Gundy-Burlet et al 19 and Dorney et al 17 concluded that the optimal combination of high efficiency occurred when the upstream stator wake was convected along the pressure surface of the downstream stator. On the contrary, He et al, 20 Hongyan et al, 16 Key et al, 18 and Fruth et al 21 observed maximum efficiency when the first stage/rotor wakes impinge on the leading edges of the second-stage rotor/stator, respectively.…”
Section: Guide Vane Rotormentioning
confidence: 99%
“…5 Quasi 3-D unsteady analyses of a 1.5 stage compressor, executed by Dorney et al, have shown that stator clocking can result in efficiency gain of 0.6-0.7%. 6 They concluded that this advantage is mainly due to the modification of the wake flow trajectory through the optimum clocking, which result in reduction in the existing losses. Cizmas and Dorney through their investigations on a 3-stage axial turbine concluded that clocking of the second stage blades is more efficient than that of the third stage.…”
Section: Introductionmentioning
confidence: 99%